2023
DOI: 10.1124/jpet.121.000921
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Non-Coding RNAs and NRF2 in Different Cancers: Spotlight on MicroRNAs and Long Non-Coding RNAs

Abstract: Cancer is a multifactorial disease and wealth of information has enabled basic and clinical researchers to develop a better conceptual knowledge of highly heterogeneous nature of cancer. Deregulations of spatiotemporally controlled transduction pathways played central role in cancer progression. NRF2-driven signaling has engrossed significant attention because of its fundamentally unique features to dualistically regulate cancer progression. Context dependent diametrically opposed roles of NRF2-induced signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…MitoQ can maintain mitochondrial metabolism and dynamic stabilization through affecting the expression of ncRNAs ( 34 ). ncRNA can interactive Nrf2 or Bcl-2 signaling pathways ( 34 , 35 ). In the future, the regulation of ncRNAs induced by MitoQ would be explored.…”
Section: Discussionmentioning
confidence: 99%
“…MitoQ can maintain mitochondrial metabolism and dynamic stabilization through affecting the expression of ncRNAs ( 34 ). ncRNA can interactive Nrf2 or Bcl-2 signaling pathways ( 34 , 35 ). In the future, the regulation of ncRNAs induced by MitoQ would be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Following KEGG enrichment analysis showed that these differentially expressed genes were mainly enriched in the Nrf2/Keap‐1 pathway. Noncoding RNA‐mediated regulation of NRF2 and interplay between Nrf2 and noncoding RNAs have added new layers of complexity to already intricate nature of Nrf2, while there are little clues about interplay between circRNAs and Nrf2 in cancers 18 . Interestingly, circKEAP1 has been suggested to competitively bind to microRNA (miRNA)−141‐3p and relived miR‐141‐3p suppression for its host gene (Keap‐1), thus suppressing the LUAD progression via the Nrf2/Keap‐1 pathway 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNA-mediated regulation of NRF2 and interplay between Nrf2 and noncoding RNAs have added new layers of complexity to already intricate nature of Nrf2, while there are little clues about interplay between circRNAs and Nrf2 in cancers. 18 Interestingly, circKEAP1 has been suggested to competitively bind to microRNA (miRNA)−141-3p and relived miR-141-3p suppression for its host gene (Keap-1), thus suppressing the LUAD progression via the Nrf2/Keap-1 pathway. 19 Our mechanistical investigations revealed that circPIBF1 silencing could prevent the nuclear translocation of Nrf2.…”
Section: Overexpression Of Ep300 or Sod2 Impairs The Repressing Effec...mentioning
confidence: 99%
“…Non-coding RNAs are categorized into different RNAs, such as microRNAs (miRNAs) (71)(72)(73)(74)(75)(76)(77)(78)(79), long noncoding RNAs (lncRNAs) (80)(81)(82)(83) and circular RNAs (84)(85)(86). Research to date makes it clear that non-coding RNAs are central components of a complex interactome that underlies cancer onset and progression.…”
Section: Regulation Of Mirnas By Nobiletinmentioning
confidence: 99%